Effectiveness of Civic Political Literacy Through Collaboration Between Schools and NGOs in Makassar City - Anjarsari, Riya; Rusnaini, Rusnaini; Nuryadi, Muhammad Hendri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The low political literacy of citizenship is an urgency in building community participation, so real efforts are needed to increase public understanding and awareness of political issues. This study explores LAPAR SULSEL’s role in the civic political literacy program in Makassar City in providing information, implementing political education, and collaborating with other institutions to achieve program goals. This research was conducted using descriptive qualitative research methods. The results showed that LAPAR SULSEL has a significant role in increasing civic political literacy in Makassar City. They provide information through publications on social media, seminars, discussions, and training using educational and advocacy strategies to build public awareness about political issues. In this research it can be concluded that through the provision of information and effective political education programs, LAPAR SULSEL has succeeded in helping people become more active and aware of their rights and obligations as citizens. Therefore, this study has positive implications for the development of civic political literacy by emulating the efforts of LAPAR SULSEL in providing information and conducting political education